The Relationship Between the Strategic Planning ‎Indicators and University Performance at University of ‎Aden - Hamza, Aswan (Jordan Journal of Educational Sciences, 2020)
The study aimed at investigating the relationship between the strategic planning indicators and university performance from graduate and postgraduate students' perspective at Aden University. To achieve this aim, an identification of the degrees of the availability of strategic planning indicators and university performance was developed in order to find out any significant differences between students' average response to the strategic planning indicators and university performance due to specialization and educational level variables. The study sample involved (144) stratified selected students. Two instruments were developed, the first for the strategic planning indicators, and the second for university performance. The results showed moderate degrees of availability of the strategic palnning indicators and university performance. Regarding specialization variable, there were differences in the first instrument, whole scale, along with its mission and goals subscales. Additionally, there were differences in the second instrument whole scale and its all subscales in favor of students of administration. Concerning the educational level variable, there were differences in mission and goals subscales, and the second instrument whole scale and its all subscales, in favor of post-graduate students. Regarding the interaction level interaction, there were differences in educational process subscale, in favor of post-graduate students of administration. The results also showed a strong positive correlation between the indicators of strategic planning and university performance.